Dependent and paranoid personality patterns in myotonic dystrophy type 1. (3rd September 2013) - Peric, S.; Sreckov, M.; Basta, I.; Lavrnic, D.; Vujnic, M.; Marjanovic, I.; Rakocevic Stojanovic, V.
<x xml:space="preserve">Abstract</x> Objectives To analyze frequency and type of personality pattern in patients with myotonic dystrophy type 1 (DM1), to correlate these findings with clinical data, and to assess its possible influence on quality of life (QoL). Materials and Methods This cross‐sectional study comprised 62 patients with DM1. Following measures were used: Muscular Impairment Rating Scale, Raven's Standard Progressive Matrices (RSPM), Millon Multiaxial Clinical Inventory I (MMCI), SF‐36, and Individualized Neuromuscular Quality of Life (INQoL) questionnaires. Results The presence of at least one pathological personality trait with score above 85 on MMCI was found in 47 (75.8%) patients. After clinical interview, 36 (58.1%) subjects had significant personality impairment. The most common personality trait in our cohort of patients was dependent found in 51.6% of patients, followed by paranoid (38.7%). Higher score on dependent personality scale correlated with lower education (rho = −0.251, P = 0.049). Dependent personality scores significantly differed between patients with physical and intellectual work (93.1 ± 8.9 vs 66.9 ± 31.7, P = 0.011). Paranoid score was higher in patients with lower education (rho = −0.293, P = 0.021), lower score on RSPM test (rho = −0.398, P = 0.004) and larger number of CTG repeats (rho = 0.254, P = 0.046). Presence of dependent personality was not in association with QoL scores (P > 0.05). On the other hand, patients with paranoid personality trait had worse QoL than those without it (P < 0.05). Conclusion Almost 60% of our patients with DM1 had clinically significant personality impairment, with dependent and paranoid personality patterns being the most common. Paranoid personality may decrease QoL in these patients, which gives us new opportunities for symptomatic therapy in DM1.